Long-term outcomes of the recovery approach in a high-security mental health setting: a 20 year follow-up study - Thomson, Lindsay; Rees, Cheryl (Frontiers in Psychiatry, 2023)
Background This study examined the outcomes of a descriptive, longitudinal cohort consisting of 241 patients initially examined in a population study at the high secure State Hospital for Scotland and Northern Ireland in 1992–93. A partial follow-up focusing on patients with schizophrenia was conducted in 2000–01, followed by a comprehensive 20 year follow-up that began in 2014. Aims To explore what happens to patients who required high secure care during a 20 year follow-up period. Method Previously collected data were amalgamated with newly collected information to examine the recovery journey since baseline. Various sources were employed, including patient and keyworker interviews, case note reviews, and extraction from health and national records, and Police Scotland datasets. Results Over half of the cohort (56.0%) with available data resided outside secure services at some point during the follow-up period (mean 19.2 years), and only 12% of the cohort were unable to transition out of high secure care. The symptoms of psychosis improved, with statistically significant reductions observed in reported delusions, depression, and flattened affect. Reported sadness [according to the Montgomery–Åsberg Depression Rating Scale (MADRS)] at baseline, first, and 20 year follow-up interviews was negatively correlated with the questionnaire about the process of recovery (QPR) scores at the 20 year follow-up. However, qualitative data depicted progress and personal development. According to societal measures, there was little evidence of sustained social or functional recovery. The overall conviction rate post-baseline was 22.7%, with 7.9% violent recidivism. The cohort exhibited poor morbidity and mortality, with 36.9% of the cohort dying, primarily from natural causes (91%). Conclusions Overall, the findings showed positive outcomes in terms of movement out of high-security settings, symptom improvement, and low levels of recidivism. Notably, this cohort experienced a high rate of deaths and poor physical morbidity, along with a lack of sustained social recovery, particularly among those who had negotiated a path through services and who were current residents in the community. Social engagement, enhanced during residence in low secure or open ward settings, diminished significantly during the transition to the community. This is likely a result of self-protective measures adopted to mitigate societal stigma and the shift from a communal environment. Subjective depressive symptoms may impact broader aspects of recovery.